TAAR1 and Psychostimulant Addiction - Liu, Jianfeng (Cell Mol Neurobiol, 2020)
Trace amine-associated receptor 1 is one of the best-characterized receptors of trace amines. Growing evidence shows that TAAR1 negatively regulates the monoaminergic activity, including dopamine transmission in the mesocorticolimbic system. Neural chemical assays demonstrated that selective TAAR1 full and partial agonists were effective to prevent psychostimulants-induced dopamine transmission in vitro and in vivo. In the last decades, many preclinical models of psychostimulant addiction such as drug-induced behavioral sensitization, drug-induced conditioned place preference, drug self-administration, drug discrimination, and relapse models were used to assess the effects of TAAR1 agonists on psychostimulants’ actions. In general, activation of TAAR1 attenuated while knockout of TAAR1 potentiated psychostimulants-associated behaviors of abuse. Here we review the advances in TAAR1 and its agonists in modulating psychostimulant addiction. We discuss the similarities and differences between the neural chemical and behavioral effects of TAAR1 full and partial agonists. We also discuss several concerns including abuse liability, sleep reduction, and species-dependent effects that might affect successful translation of TAAR1 agonists from preclinical studies to clinical application. In conclusion, although further investigations are in need to address some concerns and the underlying neural mechanisms, TAAR1 agonists are a class of promising pharmacotherapy to treat psychostimulant addiction and prevent relapse.